Pengembangan Sistem Informasi Pendakian Gunung “AyoMuncak” Berbasis Website dengan Pemanfaatan Data Geospasial - Hijriah, Az Zahra; Fajri, Ika Nur; Nugroho, Agung (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2025)
The increasing public interest in mountain hiking tourism in Indonesia has not been fully supported by the availability of accurate and integrated hiking information. This study aims to develop a web-based mountain hiking information system utilizing geospatial data to provide centralized and interactive information on hiking routes, weather forecasts, and hiker experiences. The system, named AyoMuncak, integrates interactive maps using Leaflet.js and weather data from the OpenWeatherMap API, and supports user-generated reviews. The system was developed using the waterfall model, which includes communication, planning, modeling, construction, and testing phases. Black box testing was used to ensure functional requirements were met. The results show that the system successfully delivers comprehensive information about 26 mountains in East Java, featuring mountain lists, location maps, weather forecasts, and review management. The system has been tested and proven to meet both user and admin needs. It is expected to enhance safety, convenience, and trip planning for hikers, while promoting the digitalization of tourism services based on spatial data.